Perancangan Alat Bantu Untuk Pemasangan Hanger Y4l Ke Daisa di PT XYZ - Pradityo Abimanyu; Kardiman Kardiman; Oleh Oleh (Jurnal Ilmiah Wahana Pendidikan, 2022)
A simple machine is identical to its function, which makes it easier for work or business, such as cutting time to do work, can be used to change the direction of force, and can save energy expended. In a car suspension spare parts company, there is a problem moving the Y4L hanger from the Y4L hanger to the Daisa storage area in the distribution of parts from the assembly process to the painting process. The problem with this process is the removal of the Y4L hanger by two manpowers. One of the manpower lifts directly and holds a y4l hanger weighing 25 kg, and moves it a distance of ±1.5 m. based on existing problems, it is necessary to make improvements by designing proposed tools that aim to facilitate manpower work. The stage in the proposed design of the tool consists of a description of the problem, the design objectives, the design process. The final result of this research is the proposed lever design as a tool to facilitate manpower activities and can save one manpower and several wasted costs, and can cut time. The dimensions of the tool made are: 87.94 cm long, 120 cm high, 66 cm wide.